Clinical Assessment of Motor Speech Disorders in Adults with Concussion - Cannito, Michael P. (Seminars in Speech and Language, 2014)
This article reviews the occurrence of motor speech disorders of dysarthria and apraxia of speech following closed head injury and other traumatic brain injuries in adults as they apply to sport concussion and related trauma. Athletic sideline and speech-language pathology screenings are considered. Procedures for clinical assessment and diagnosis of motor speech disorder, most particularly dysarthria, are discussed with special reference to closed head injury. Included are the evaluation components of cranial nerve and speech mechanism examination, nonspeech musculature examination, perceptual and instrumental assessment procedures, quasi-standardized testing for dysarthria, and the determination of restrictions of participation in everyday life activities. The resultant output of such an evaluation is described in depth. Future directions for clinical research on motor speech disorders following sports concussion are also briefly considered.
Keywords: Motor speech disorders; concussion; traumatic brain injury; assessment and diagnosis